Dyskurs europejski i poszukiwanie europejskiej tożsamości - White, Hayden (Er(r)go. Teoria - Literatura - Kultura, 2001)
The Discourse of Europe and the Search for a European Identity Abstract in English "The Discourse of Europe and the Search for a European Identity" focuses on the problematisation of the identity of contemporary Europe. Hayden White refuses to identify contemporary Europe with its allegedly inherent goodness and dignity. He argues that Europe is by no means a clear and well defined category, and indicates that, historically, it has been characterised by hegemonic tendencies and aggression against what it could not dominate or assimilate. Thus he sees the EEC and the NATO as manifestations of the hegemonic impulses of the European civilisation. White goes on to elaborate on the far-reaching consequences of the insistence on defining identities: it paves the way for racism, class distinctions and sexism. The latter part of the essay is concerned with a discussion of "La Systeme de la mode" by Roland Barthes and its implications for our attempts at defining a European identity.